Influential factors of donation interest : the significance of risk perception and the role of cosmopolitanism - Lilja Ósk Diðriksdóttir 1989- (2015)
Based on interviews with employees of humanitarian organizations in Iceland, humanitarian organizations’ annual reports, and literature on donation, it is clear that success in gathering financial donations can vary greatly between causes. This thesis aims to find what factors contribute to these differences, more specifically, what factors can influence donation interests regarding three causes: donation to victims of natural disasters, poverty and war. A quantitative study was conducted in the form of an online survey to Icelanders to see if risk perception of a certain event can influence a person’s donation interest towards the victims of the event. The study also examined the influence of two factors of Cosmopolitanism on donation interest: the feeling of belonging to a world society, and the feeling of responsibility towards people outside a person’s inner community. The goal of this study is to contribute to the vast field of research regarding human help giving and help humanitarian organizations gain a deeper understanding of people’s donation interest regarding different causes. The main results of the study show that the three factors had a significant impact on donation interest towards victims of natural disasters, poverty and war, with a strong positive correlation. Also, there was a difference in risk perception, where participents perceived the highest risk from poverty, and the lowest to war. Additionally, there was a difference in donation interest, where the lowest interest was towards victims of war, which is in line with the results showing the positive correlation of risk perception and donation interest. Keywords: humanitarian organizations, donation interest, risk perception, Cosmopolitanism, natural disasters, poverty, war